OPTIMASI PENJADWALAN PRODUKSI MENGGUNAKAN PENDEKATAN ALGORITMA HARMONY SEARCH DI PT ADI SATRIA ABADI (ASA - Inaaratul Chusna Ichda Purwanto; Yohanes Anton Nugroho; Suseno Suseno (Universitas Islam Nahdlatul Ulama Jepara, 2020)
PT Adi Satria Abadi (ASA) is a company engaged in the processing of leather, especially sheep skin and goat skin, which is used for the manufacture of golf gloves. The problem faced by the company is the production process that exceeds the due date to other customers who order products at PT ASA. From the research, it is known that the cause is a company scheduling method that has not been organized so that the production sequence is concurrent. Selection of methods Harmony Search algorithms in scheduling are caused by delays. The Harmony Search algorithm can provide a better makespan value than the company method. The results of the company method obtain 0.9 months makespan average, the Harmony Search Algorithm method produces an average 0.8 months makespan. In addition, the use of the Harmony Search Algorithm method can reduce the average value of 0.1 months makespan. The results of the study in three months experienced time savings of 0.6 months, 0.6 months and 0.1 months respectively.